Implementasi Teori Pengelompokan Kegiatan Ruang Publik pada Penataan Tapak Mall di Surabaya - Adi Wiyono, Kresno; Mufidah, Mufidah; Hastijanti, Retno (Rifa'Institute, 2024)
Rising demand for retail space in Surabaya is met with concerns over the impact of online shopping on malls. This study examines the application of public space activity grouping theory to malls in Surabaya to reinforce their role as inclusive spaces. Methods include site analysis based on Edward T. White (1983) and activity analysis based on Dea et al. (2021). The study proposes a site layout divided into three zones with activities categorized by time, intensity of visits, and age of visitors: Public / Night Time Zone, Commercialized / Building Zone, and Semi Public / Day Time Zone. The proposed site zoning can be implemented on sites with similar conditions. Further research is needed to develop architectural forms with specific design approaches.